Comparison of upper limb's biomechanics parameters in tennis in terms of sports level - Maciejewski, K. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction The upper limbs play a crucial role in generating power and accuracy during various sports activities. Tennis, in particular, relies heavily on efficient upper-limb biomechanics for a successful serve. Studies have suggested that elite athletes exhibit distinct movement patterns compared to their lower-skilled counterparts (Elliot et al., 2003). However, a comprehensive understanding of how biomechanical parameters of the upper limbs differ across various skill levels in tennis serving is lacking. This study aims to investigate and compare the biomechanical parameters of the upper limbs during the tennis serve motion in athletes of varying skill levels (elite, advanced, and beginner). By analysing key movement patterns, we hope to identify specific biomechanical characteristics associated with different skill levels in tennis serving.